Generation of Islet-like Cell Aggregates from Human Adipose Tissue-derived Stem Cells by Lentiviral Overexpression of PDX-1 - Bahrebar, M. (Int J Organ Transplant Med, 2015)
BACKGROUND: Pancreatic duodenal homeobox1 (PDX-1) is a transcription factor that is important in regulating pancreas development and maintaining β-cell function. β-cell replacement is an effective approach for the treatment of type 1 diabetes. Human adipose-mesenchymal stem cells (hAMSCs) are the ideal population cells for differentiating into insulin-producing cells. OBJECTIVE: To determine if islet-like cell aggregates production could be generated from hAMSCs by lentiviral overexpression of PDX-1. METHODS: After isolation of hAMSCs, characteristics of these cells were identified by flow-cytometic analysis and multilineage differentiation studies. PDX-1 gene delivered into hAMSCs through lentiviral vector for differentiating hAMSCs into insulin-producing cells (IPCs) at the utilized protocol for 14 days. Characteristics of IPCs were evaluated by immunocytofluorescence, dithizone staining, and quantitative reverse transcription PCR. In response to high glucose medium, insulin release was detected by chemiluminescence enzyme immunoassay. RESULTS: The islet-like cell aggregates appeared about 10 days after introduction of PDX-1 into hAMSCs. PDX-1 induced its own expression (auto-induction), a number of islet-related genes such as Ngn3, Nkx2-2, and insulin. The insulin-positive cells were detected in the PDX-1 transduced cells. In response to glucose challenge test, secretion of insulin hormone in the medium with high glucose concentration significantly increased in the PDX-1-transduced cells related to medium with low glucose concentration. CONCLUSION: Introduction of lentiviral PDX-1 significantly induces hAMSCs to differentiate into islet-like cell aggregates, which may provide a source of adipose stem cells-derived insulin-producing cells for cell replacement therapy in type 1 diabetes.